2020
DOI: 10.3390/antiox9090795
|View full text |Cite
|
Sign up to set email alerts
|

Cyst Nematode Infection Elicits Alteration in the Level of Reactive Nitrogen Species, Protein S-Nitrosylation and Nitration, and Nitrosoglutathione Reductase in Arabidopsis thaliana Roots

Abstract: Reactive nitrogen species (RNS) are redox molecules important for plant defense against pathogens. The aim of the study was to determine whether the infection by the beet cyst nematode Heterodera schachtii disrupts RNS balance in Arabidopsis thaliana roots. For this purpose, measurements of nitric oxide (NO), peroxynitrite (ONOO−), protein S-nitrosylation and nitration, and nitrosoglutathione reductase (GSNOR) in A. thaliana roots from 1 day to 15 days post-inoculation (dpi) were performed. The cyst nematode i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In this study, we identified several ER chaperones and key enzymes in protein glycosylation, folding, transport, and lipid biosynthesis which undergo S-nitrosylation (Table 1). Consistently, GSNOR1 is known to locate in ER 60 , and dysfunction of GSNOR1 in the gsnor1/hot5 mutants leads to the increased expression of ER-stress responsive genes, like BiPs, ERDJ3A, and SHD, resulting in an insensitive response to Tm-induced ER stress. The mutants that lack S-nitrosylation target proteins, such as crt1a or ebs1, also showed altered sensitivity to Tm 61,62 .…”
Section: Discussionmentioning
confidence: 75%
“…In this study, we identified several ER chaperones and key enzymes in protein glycosylation, folding, transport, and lipid biosynthesis which undergo S-nitrosylation (Table 1). Consistently, GSNOR1 is known to locate in ER 60 , and dysfunction of GSNOR1 in the gsnor1/hot5 mutants leads to the increased expression of ER-stress responsive genes, like BiPs, ERDJ3A, and SHD, resulting in an insensitive response to Tm-induced ER stress. The mutants that lack S-nitrosylation target proteins, such as crt1a or ebs1, also showed altered sensitivity to Tm 61,62 .…”
Section: Discussionmentioning
confidence: 75%
“…The potential association between DE-lncRNAs and a RING/U-box superfamily gene, an Aldolase-type TIM barrel family gene, laccase7, ARF8, a MYB domain-containing gene, and several HSPs, which are involved in resistance to SCN (Zhao et al, 2017;Ul Haq et al, 2019;Cheng et al, 2020;Hishinuma-Silva et al, 2020), brings new insights into the SCN-soybean interaction. Moreover, the association between lncRNAs and nitrite reductase as a major gene in reactive nitrogen species (RNS) metabolism and plant defense against the beet cyst nematode (Labudda et al, 2020), ACC oxidase which is involved in ethylene-based signal transduction and regulates the attractiveness of soybean roots to SCN (Tucker et al, 2010;Hu et al, 2017), galactinol synthase and drought-induced gene as neighboring nematode defenserelated protein-coding genes (Kandoth et al, 2011), and NAC and MADS-box as key TFs involved in soybean defense response under RKN invasion (de Sá et al, 2012) provides important notes for further characterization of SCN resistance genes in soybean. The possible association between DE-lncRNAs and the pectin lyase-like superfamily protein as a pectin-degrading enzyme suggests pectin lyase-like superfamily gene/DE-lncRNA interaction-mediated defense signals via modification of cell wall integrity and lignin content, which is consistent with the obtained results in previous studies (Gallego-Giraldo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The GSNOR level was enhanced in infected roots at 3 dpi and 7 dpi, but at 15 dpi, did not differ between uninfected and infected roots. The GSNOR was observed in plastids, mitochondria, the cytoplasm, as well as in the endoplasmic reticulum and cytoplasmic membranes [236].…”
Section: Nematodesmentioning
confidence: 96%